Damage limit states for confined masonry walls based on experimental test - Zavala, Carlos (2019)
Non engineering dwellings represents 83% of the stock of housing in emerging areas of Lima city. These dwellings are build with non-appropriated masonry bricks with walls that limits don´t meet the displacement control of the earthquake design standards NTE-030 and NTE-070. Considering the database of structural test of 33 years of experimental studies of the Structural Laboratory of CISMID, typical behavior curves are studied in order to propose damage limit state for masonry walls: build with industrial bricks, build with handmade bricks and build with horizontal hollow tubular bricks. Also, results of full-scale test on masonry house performed in the laboratory are studied. Ranges of inelastic development limit states of walls are proposed from the test results of full-scale test of the three types of masonry. Big difference in the capacity of walls with tubular bricks in comparison with the others types are found. Also limit drift values threshold are propose to be use in the analytical modelling of wall structures with handmade or tubular bricks. These proposal limits are smaller than the limit of NTE-030 standard.